Growth promotion in pigs by oxytetracycline coincides with down regulation of serum inflammatory parameters and of hibernation‐associated protein HP‐27. Issue 10 (18th March 2016) - Soler, Laura; Miller, Ingrid; Hummel, Karin; Razzazi‐Fazeli, Ebrahim; Jessen, Flemming; Escribano, Damian; Niewold, Theo
Abstract : The growth promoting effect of supplementing animal feed with antibiotics like tetracycline has traditionally been attributed to their antibiotic character. However, more evidence has been accumulated on their direct anti‐inflammatory effect during the last two decades. Here we used a pig model to explore the systemic molecular effect of feed supplementation with sub therapeutic levels of oxytetracycline (OTC) by analysis of serum proteome changes. Results showed that OTC promoted growth, coinciding with a significant down regulation of different serum proteins related to inflammation, oxidation and lipid metabolism, confirming the anti‐inflammatory mechanism of OTC. Interestingly, apart from the classic acute phase reactants also down regulation was seen of a hibernation associated plasma protein (HP‐27), which is to our knowledge the first description in pigs. Although the exact function in non‐hibernators is unclear, down regulation of HP‐27 could be consistent with increased appetite, which is possibly linked to the anti‐inflammatory action of OTC. Given that pigs are good models for human medicine due to their genetic and physiologic resemblance, the present results might also be used for rational intervention in human diseases in which inflammation plays an important role such as obesity, type 2 diabetes and cardiovascular diseases.